Síntese de derivados de diidrocumarinas assistida por irradiação de micro-ondas e avaliação da atividade anticolinesterásica - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by irreversible and progressive loss of memory and cognitive functions. It is the most common form of dementia in the elderly, which can represent up to 80 % of cases and still existing treatments are only symptomatic and very restricted. The main class of drugs used for AD are acetylcholinesterase inhibitors (AChE) as tacrine, donepezil, rivastigmine and galantamine, which do not contribute significantly to long-term improvements in cognitive and behavioral functions, besides that their action is not always successful, justifying the search for inhibitors of AChE more potent and less toxic. To this end, several classes of compounds have been studied. Among these compounds with possible anticholinesterase actions are the dihydrocoumarins, which are neoflavonoids, coumarin derivatives with a demostrated diverse pharmacological potential. The aim of this study was to synthesize replaced dihydrocoumarins derivatives using radiant heating microwave and evaluate, in vitro, the anticholinesterase activity of this series of dihydrocoumarins using microplate assay with Ellman's reagent. Seven compounds were synthesized and all showed the ability to inhibit AChE, with percentages between 0.4 and 39 % inhibition, two of which (5b, 3b) can be considered as prototypes for a new class of compounds able to perform acetylcholinesterase activity, and thus promote the treatment of AD.
Keywords: Doença de Alzheimer (DA); Acetilcolinesterase (AchE); Síntese; Micro-ondas; Diidrocumarinas; Alzheimer's Disease (DA); Acetylcholinesterase; Dihydrocoumarins; Synthesis; Microwave; CIENCIAS EXATAS E DA TERRA::QUIMICA